2008
DOI: 10.1021/jm8000345
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Series of Biphenyl Benzoic Acid Derivatives as Highly Potent and Selective Human β3 Adrenergic Receptor Agonists with Good Oral Bioavailability. Part II

Abstract: The left-hand side (LHS) and central part of our first generation biphenyl (FGB) series was modified to improve in vitro and in vivo beta3-AR potency without loss of oral bioavailability. First, in this study, we focused our efforts on replacement of the 3-chlorophenyl moiety in the LHS of FGB analogues with 3-pyridyl ring analogues to adjust the lipophilicity. Second, we investigated the replacement of the central part of this series and discovered that introduction of a methyl group into the alpha-position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…To address this problem, a series of second generation biphenyl (SGB) analogues were developed, with adjustment of physical properties by replacement of the phenyl moiety with pyridine analogues on the left-hand side (LHS), resulting in enhanced potency and maintenance of good oral availability as shown in Table 1. 11 In a previous metabolism study of FGB/SGB analogues conducted in rat and human hepatocytes, we identified two main metabolites: a dealkylated metabolite (M-1) and an acylglucuronide conjugated metabolite (M-2) as shown in Scheme 1. 12 Although glucuronide metabolites from phase II metabolism generally enhance elimination in bile and urine, they can also transform into their covalent adducts which can lead to toxicity.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…To address this problem, a series of second generation biphenyl (SGB) analogues were developed, with adjustment of physical properties by replacement of the phenyl moiety with pyridine analogues on the left-hand side (LHS), resulting in enhanced potency and maintenance of good oral availability as shown in Table 1. 11 In a previous metabolism study of FGB/SGB analogues conducted in rat and human hepatocytes, we identified two main metabolites: a dealkylated metabolite (M-1) and an acylglucuronide conjugated metabolite (M-2) as shown in Scheme 1. 12 Although glucuronide metabolites from phase II metabolism generally enhance elimination in bile and urine, they can also transform into their covalent adducts which can lead to toxicity.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous study, we described a series of first generation biphenyl (FGB) analogues, shown in Figure , which exhibited good oral bioavailability and a long plasma half-life . The key to success was finding a benzoic acid moiety and R substitution on the right-hand side (RHS) which maximized β 3 -AR activity, selectivity, and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the catalytic hydrogenation to obtain amino alcohol ( R )- 15 , using conditions identical to those used for the other substrates, only a slight decrease in enantiomeric excess was observed (97% to 94%). In order to reduce the amide to an amine without reducing the ester functionality, we used a modified literature procedure employing borane dimethylsulfide complex; this transformation gave the known compound ( R )- 16 with an enantiomeric excess of 95%. Final hydrolysis of the ester function to the carboxylic acid was accomplished following a literature procedure using LiOH .…”
mentioning
confidence: 99%